Analisis Hukum terhadap Anak yang Sudah Kawin sebagai Subyek yang Berhadapan dengan Hukum (Studi Kasus Putusan Pengadilan Negeri Sampit Nomor: 03/Pid.Sus Anak/2015/PN.Spt) - Nanang Ibrahim Soleh; Heriamariaty; Thea Farina; Nor Asriadi (Program Pascasarjana Universitas Palangka Raya dan (and) Ikatan Ahli Teknik Penyehatan dan Teknik Lingkungan IndonesiaÂ (IATPI), 2020)
Children are gifts and entrusted from God who are given talents and dignity as a whole creature. During their lifetime, children sometimes face legal problems such as narcotics abuse. This becomes complicated while the child has been married and being a subject against the law. The determination the age limit for children is still a debate because sev-eral laws and regulations provide different figures. This is, indeed, a crucial matter because it will affect legal conse-quence to the children, especially for those who deal with narcotics crime. Based on this point of departure, the authors examine Sampit District Court Decision Number: 03/Pid.SusAnak/2015/PN.Spt regarding narcotics abuse by a married child.